(untitled) (Al-Academy, 2024)
Negative space plays a pivotal role in enhancing visual perception and adding clarity and balance to logos. Negative space makes contrast between elements, making the logo more attractive and enhancing communication. Logos that strategically utilize negative space can create hidden elements that may arouse curiosity and enhancing the process of conveying meaning. Using negative space based on the principles of visual communication can be an effective tool for designers to enhance the interactive relationship of the logo. Employing gestalt principles, such as proximity, closure, and shape against the background, is an effective way to exploit negative space in a way that make the visual message more transnational. Negative space is a tool that connects elements of the logo and simplifies meanings. This research is based on studying a selection of logos that used negative space to determine the impact of its use and methods of employing it in logo design.